2016
DOI: 10.1177/0040517516671128
|View full text |Cite
|
Sign up to set email alerts
|

Properties and performances of fabrics made from bio-based and degradable polylactide acid/poly (hydroxybutyrate- co-hydroxyvalerate) (PLA/PHBV) filament yarns

Abstract: This paper reports a comparative experimental study of single jersey knitted fabrics made from a novel bio-based and degradable polylactide acid/poly (hydroxybutyrate-co-hydroxyvalerate) (PLA/PHBV) multi-filament yarn, together with polylactide acid , Cupro, polyethylene terephthalate (PET) and polyamide 6 (PA 6) multi-filament yarns. Their structures, mechanical, thermal and surface properties and performances as well as anti-bacterial behavior are measured and compared. It has been found that the polylactid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…A comparison of the mechanical, thermal, and surface properties, as well as the anti-bacterial behavior, of five different types of synthetic multi-filament yarn and the corresponding knitted fabrics was presented in the work of Huang et al [96]. Three biobased materials (PLA/PHBV, PLA, Cupro) and two petroleum-based materials (PET, PA6) were considered.…”
Section: Mechanical Performancementioning
confidence: 99%
“…A comparison of the mechanical, thermal, and surface properties, as well as the anti-bacterial behavior, of five different types of synthetic multi-filament yarn and the corresponding knitted fabrics was presented in the work of Huang et al [96]. Three biobased materials (PLA/PHBV, PLA, Cupro) and two petroleum-based materials (PET, PA6) were considered.…”
Section: Mechanical Performancementioning
confidence: 99%
“…In addition to conventional PLA filament, PLA resin can be blended with other materials such as PBS and poly (hydroxybutyrate-co-hydroxyvalerate) (PHBV) to spin blended filament through the spinning process. [53][54][55] Hassan et al 55 fabricated PLA/PBS blended filaments with five different blending ratios for healthcare products. The proportions of PBS of the blended filaments were 0, 3%, 6%, 9% and 12%.…”
Section: Spinning Of Pla Filamentsmentioning
confidence: 99%
“…Gerard and Zembouai et al studied the morphology and mechanical properties of PLA/PHBV blends, and Huang et al studied the properties of weft knits of PLA/PHBV blended yarns. The results showed that the PLA/PHBV yarn woven fabric had excellent antibacterial properties [4,5,6,7]. Zhang et al studied the dyeing process of PLA and PHBV blends.…”
Section: Introductionmentioning
confidence: 99%